Skin Rejuvenation Profile in Dr. Soetomo General Hospital Surabaya - Lutfia Ariska Ramadhani; Trisniartami Setyaningrum; Etty Hary Kusumastuti (Health Notions, 2019)
Skin aging is a condition in which cell and tissue changes occur due to mechanism abnormalities and a decrease in function of a tissue which can be triggered by intrinsic or extrinsic factors. Intrinsic factor is an aging process which originates from the body of an individual itself while extrinsic factor is an aging process caused by factors from the outside, such as excessive exposure to the UV light, smoking, or poor nutrition. Skin rejuvenation therapy, hopefully, would be able to restore or even slow down the aging process itself. This research was a descriptive observational using retrospective approach based on patients’ medical record in the Outpatient Clinic of Dermatology and Venereology Department in Dr. Soetomo General Hospital Surabaya in January to December 2017. This study obtained 203 samples (198 women/females and 5 men/males) with the most age group ranging from 45-